Association between anger expression and attempted suicide at a general emergency hospital in the south of Brazil - Zatti,Cleonice (2021)
Abstract Introduction Suicide is one of the leading causes of death in the world. For every person who commits suicide, twenty or more have attempted to take their own lives. The emotional state of anger is often associated with suicidal behavior. However, this association needs to be further clarified. Objectives This study sought to investigate the profiles of traits and expressions of anger in inpatients admitted to a general emergency hospital after surviving a suicide attempt. Methods In this case-control study, a sample of 28 suicide survivors was matched for sex, age, and educational level with 56 controls. The State-Trait Anger Expression Inventory-2 was used to measure anger traits and expression. Results Suicide survivors scored higher for anger traits and expression and lower for anger control than the control group. They also had lower levels of state anger and willingness to express anger verbally than the control group. Conclusions Patients who attempted suicide and had high scores for anger expression (in and out) are inclined to have extreme difficulty in interpersonal relationships and rigidity towards change and are at higher risk of developing psychopathologies.